Regulatory T Cells As Supporters of Psychoimmune Resilience: Toward Immunotherapy of Major Depressive Disorder - Ellul, Pierre; Mariotti-Ferrandiz, Encarnita; Leboyer, Marion; Klatzmann, David (Frontiers in Neurology, 2018)
There is growing evidence that inflammation plays a role in major depressive disorder (MDD). As the main role of regulatory T cells (Tregs) is to control inflammation, this might denote a Treg insufficiency in MDD. However, neither a qualitative nor a quantitative defect of Tregs has been ascertained, and no causality direction between inflammation and depression has been established. Here, after reviewing the evidence supporting a relation between Treg insufficiency and MDD, we conclude that a novel therapeutic approach based on Treg stimulation could be valuable in at least the subset of patients with inflammatory MDD. Low-dose interleukin-2 appears to be a good candidate as it is not only a safe stimulator of Tregs in humans, but also an inhibitor of pro-inflammatory Th17 lymphocytes. Here we discuss that thorough immune investigation as well as immunotherapy will be heuristic for deciphering the pathophysiology of MDD.